FTO/EFNB2 Axis Protects Retinal Ganglion Cells Against H2O2-Induced Oxidative Damage - Yi Yin; Zhaoyang Meng; Yu Wang; Binbin Zhan; Yan Zhang; Zhenxi Xia (Discovery Medicine, 2026)
Background: Traumatic optic neuropathy (TON) causes progressive retinal ganglion cell (RGC) loss and oxidative injury, leading to visual dysfunction. Ephrin B2 (EFNB2) is elevated in optic nerve injury; however, it is unclear how the fat mass and obesity-associated gene (FTO) regulates it upstream. This study examined whether RGCs are shielded from hydrogen peroxide (H2O2)-induced oxidative damage through FTO-mediated EFNB2 overexpression.Methods: Primary RGCs were isolated and exposed to H2O2 to establish an in vitro oxidative stress injury model. We first verified the concentration-dependent induction of FTO and EFNB2 by H2O2. Gain- and loss-of-function assays were performed using FTO overexpression and knockdown plasmids to assess its effects on RGC viability, apoptosis, reactive oxygen species (ROS) accumulation, caspase-3 activity, and the expression of EFNB2, erythropoietin-producing hepatoma receptor B4 (EPHB4) and apoptosis-related proteins. Rescue experiments with EFNB2 knockdown were further conducted to confirm whether EFNB2 acts as a downstream effector of FTO.Results: H2O2 treatment elevated FTO and EFNB2 expression in RGCs in a concentration-dependent manner (p < 0.01). FTO overexpression alleviated H2O2-induced reductions in cell viability, as well as increases in apoptosis, caspase-3 activation, and ROS levels (p < 0.001), while FTO knockdown exacerbated these injuries (p < 0.001). Moreover, FTO overexpression enhanced EFNB2 and EPHB4 expression, and suppressed Bax and cleaved caspase-3 levels (p < 0.001). Knockdown of EFNB2 reversed the protective effects of FTO overexpression on RGC survival, oxidative stress, and apoptosis (p < 0.001).Conclusions: FTO upregulates EFNB2 and EPHB4 expression, reduces ROS and apoptosis, and is associated with the protection of RGCs against H2O2-induced oxidative damage. The FTO/EFNB2 axis may represent a protective mechanism against oxidative damage in RGCs in vitro, warranting further investigation in traumatic optic neuropathy models.